2018
DOI: 10.1007/s10933-018-0030-3
|View full text |Cite
|
Sign up to set email alerts
|

Mining pollution triggered a regime shift in the cladoceran community of Lake Kirkkojärvi, southern Finland

Abstract: Mining is one of the key industries in the world and mine water pollution is a serious threat to aquatic ecosystems. Historical monitoring data on the pollution history and impacts in aquatic ecosystems, however, are rarely available, so paleolimnological methods are required to explore the consequences of past pollution. We studied the history of cladoceran community dynamics in Lake Kirkkojärvi, southern Finland, including the periods before, during and after mining. We analyzed the geochemical composition a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…In the water column, tailings influence plankton dynamics by increasing inorganic turbidity. Inorganic turbidity represents an essential regulator of species dynamics and trophic interactions, weakening the link between phytoplankton, zooplankton, and high trophic levels (Guenther & Bozelli 2004; Horppila & Liljendahl‐Nurminen 2005; Leppänen et al 2018). Since the beginning of the restoration activities in Batata Lake, considerable improvements in water clarity were observed in the impacted areas (Bozelli et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In the water column, tailings influence plankton dynamics by increasing inorganic turbidity. Inorganic turbidity represents an essential regulator of species dynamics and trophic interactions, weakening the link between phytoplankton, zooplankton, and high trophic levels (Guenther & Bozelli 2004; Horppila & Liljendahl‐Nurminen 2005; Leppänen et al 2018). Since the beginning of the restoration activities in Batata Lake, considerable improvements in water clarity were observed in the impacted areas (Bozelli et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…5). C. sphaericus is a resilient taxon (Koff et al, 2016) and has been often found to increase under environmental perturbation, such as eutrophication (Nevalainen and Luoto, 2013) and mining pollution (Leppänen et al, 2018). Although usually considered as a littoral cladoceran, C. sphaericus can thrive in the plankton of eutrophic lakes as well (Manca et al, 2007).…”
Section: Planktonic Communitiesmentioning
confidence: 99%
“…B. longirostris is regarded as more sensitive to copper pollution than many other cladoceran species (Koivisto et al 1992;Koivisto and Ketola 1995;Bossuyt and Janssen 2005) which may explain the above mentioned deleterious impact. Leppänen et al (2017b) reported decreased diversity and species richness in Lake Kirkkojärvi, southern Finland, which has been affected by increased input of mineral matter and minor metal pollution, originating from tailings impoundment of Au-Cu mine around 1960-1970, but the lake has never acidified due to rapid dilution. The most pronounced impact was detected during the input of fine mineral tailings.…”
Section: Cladocera and Metal Miningmentioning
confidence: 99%